Avaliação in vitro da atividade biológica e identificação de componentes da secreção larval de Lucilia cuprina e Sarconesia chlorogaster (Diptera, Calliphoridae) frente à protozoários e linhagens celulares - Garzon, Litiérri Razia (2022)
Diptera of the Calliphoridae family play an important role in forensic analysis, veterinary and medical science. Its use in biotherapy is well known and important due to the biological activity of the larvae and the constituents of their secretion that help in tissue healing. An advantage of using larval secretion is the low toxicity in normal cells, little or no side effects with low production cost. This work evaluated the in vitro biological activity of larval secretion of L. cuprina and S. chlorogaster in protozoa and cell lines. In the first study, the secretion of L. cuprina was evaluated against L. amazonensis promastigotes, T. cruzi epimastigotes, B16-F10 tumor lineage and HFF-1 non-tumor cell lineage to evaluate cytotoxicity and safety. The results revealed that the secretion was effective in reducing the viability of parasites and tumor cells. It also proved to be safe against the fibroblast lineage. In the second study, secretions of L. cuprina and S. chlorogaster were evaluated against other tumor cell lines (A549, A375 and Hela), antiproliferative activity, DNA cleavage and identification of constituents by mass spectrometry. The results showed the ability of L. cuprina to reduce cell viability and increase reactive oxygen and nitrogen species against tumor cell lines A549, A375 and HeLa in all tests applied VN, ON, MTT, LDH, Adherence and DCFH-DA. Both secretions exerted antiproliferative activity and were able to cleave plasmid DNA. Regarding the analysis of the constituents, it was possible to identify components such as fatty acid, cembranoid valine, stearoylhistidine and tripeptide in the secretion of L. cuprina. The secretion of S. chlorogaster presented chemical structures not recognized in the database, suggesting the possibility of unpublished components. Taken together, the presented results demonstrate that dipteran secretion becomes an important resource to be analyzed due to its biological properties with in vitro action against protozoa and carcinomas.